Potential Benefits of Mixed Waste Collection Methods - Titrik, Ádám (Periodica Polytechnica Transportation Engineering, 2023)
It is difficult to determine the ideal way for collecting selective waste since calculations must be made taking into account a variety of collection vehicles, containers, city regions, and verifying vehicles. Additionally, we need to keep in mind that acquiring some statistical information on container filling is crucial for organizing the gathering process. The majority of the vehicles used for the gathering operate on fossil fuels like gasoline, which releases carcinogens into the atmosphere. Since the engine drives a hydraulic pump that generates power to lift the container when it is being emptied, the exhaust emissions are not solely coming from the vehicles when they reach the container. As a result, it is crucial to describe the entire gathering process. On the one hand, we want to safeguard the environment by utilizing selective gathering, but on the other hand, there are gathering vehicles that emit carcinogenic exhaust gas. In order to reduce unneeded pollution from the gathering vehicle, we aim to identify the best solution in this paper for choosing the appropriate selective material collection method.